Answer:
x=a−h,y=a,z=a+h then you have the following trigonometric identity
sin(a−h)=sinacosh−cosasinh
sin(a+h)=sinacosh+cosasinh
cos(a−h)=cosacosh+sinasinh
cos(a+h)=cosacosh−sinasinh
[tex]\frac{sin(a-h)+sina+sin(a+h)}{cos(a-h)+cosa+cos(a+h)}[/tex]
[tex]\frac{sina(2cosh+1)}{cosa(2cosh+1)}[/tex]
sina/cosa=tana
recall that a=y
sina/cosa=tany
Step-by-step explanation:
Show that if $x$, $y$, and $z$ are consecutive terms of an arithmetic sequence, with $x \leq y \leq z$, and both sides of the equation are defined, then?
the complete part of the question will be what follows
[tex]\frac{sinx+siny+sinz}{cosx+cosy+cosz} =tany[/tex]
This are trigonometric identity,
We take the terms of the Linear Sequence as
x=a−h,y=a,z=a+h then you have the following trigonometric identity
sin(a−h)=sinacosh−cosasinh
sin(a+h)=sinacosh+cosasinh
cos(a−h)=cosacosh+sinasinh
cos(a+h)=cosacosh−sinasinh
[tex]\frac{sin(a-h)+sina+sin(a+h)}{cos(a-h)+cosa+cos(a+h)}[/tex]
[tex]\frac{sina(2cosh+1)}{cosa(2cosh+1)}[/tex]
sina/cosa=tana
recall that a=y
sina/cosa=tany